(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article analyzes the methodological aspects of enhancing educational effectiveness through the integration of specialized and general education modules in the credit-module system. The role of integrative teaching in improving the efficiency of the educational process and the significance of the credit-module system in combining professional and general knowledge of students are explored. The article scientifically justifies how the integration of specialized and general modules can improve teaching effectiveness.